Pelatihan Menulis Pantun Dengan Model Concept Learning, Quantum Learning Dan Motede Menulis Berantai - Mardiah, Mardiah; Napratilora, Martina (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2024)
This study aims to improve PGMI student’s ability in STAI Auliaurrasyidin in wariting a research paper like a pantun. One of ways to improve the student’s ability I writing a research paper is introducing and teaching them about teaching and learning model of concept learning, quantum learning, and method of chain writing. The advantages of this study is the college students have ability in using the model and method in writing a pantun. Concept learning model, quantum learning, and chain writing method is one of ways that can be used in writing a pantun.